Reproductive biology and energy allocation of the sea star Cosmasterias lurida (Echinodermata: Asteroidea) from the Beagle Channel, Tierra del Fuego, Argentina - Cossi, Paula Fanny; Boy, Claudia Clementina; Giménez, Juliana; Perez, Analia Fernanda (Polar Biology)
Seasonal fluctuations in environmental factors at high-latitude marine regions have a strong influence on the reproductive cycles of echinoderms. The purposes of this study on a population of Cosmasterias lurida in the Beagle Channel are to describe the reproductive cycle through histological analyses, to characterize the pattern of gonad and somatic indices, to determine the energy content of different organs and their temporal variation and to establish the pattern of energy allocation. During the study period, from August 2010 to June 2011, four seasonal samplings were performed in the subtidal zone of Ushuaia Bay. Indices (gonad, pyloric caeca and stomach), gonadal histology, organic matter and calorimetric measurements were determined. Gametogenesis begins in February and continues until June when oocyte size increases. The gonadal maximum development and gamete releasing take place between August and December. Temporal variation of energetic reserves in gonads occurs through the variation in gonad mass, with a GI major peak and energy content during August. Stomach and pyloric caeca show their maximum energy accumulation during June, while decrease of organic matter of the body wall takes place from August to December. The population of C. lurida from Beagle Channel suggests an annual reproductive cycle with two maturation events and the influence of water temperature on maturation and releasing of gametes. Different patterns of energy allocation to gonads between sexes were observed, with a greater energy investment in females than in males. Pyloric caeca, stomach and body wall were proposed as energy reservoirs for gonadal maturation and spawning. Fil: Cossi, Paula Fanny. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Química Biológica de la Facultad de Ciencias Exactas y Naturales; Argentina. Universidad Maimónides. Area de Investigaciones Biomédicas y Biotecnológicas. Centro de Estudios Biomédicos, Biotecnológicos, ...